2017
DOI: 10.1002/lt.24743
|View full text |Cite
|
Sign up to set email alerts
|

Living donor liver transplantation during the first 3 months of life

Abstract: Living donor liver transplantation (LDLT) is now an established technique for treating children with end-stage liver disease. Few data exist about liver transplantation (LT) for exclusively young infants, especially infants of <3 months of age. We report our single-center experience with 12 patients in which LDLT was performed during the first 3 months of life and compare the results with those of older infants who underwent LT. All of the patients were treated at the National Center of Child Health and Develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
33
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 34 publications
6
33
1
1
Order By: Relevance
“…Additionally, mortality is high without liver transplantation (LT) . Transplantation in pediatric candidates with pediatric acute liver failure (PALF) is a more arduous prospect because technical and logistical features unique to children increase complexity of implantation, including donor/recipient size mismatch, poor availability of pediatric donors, and technical and ethical concerns surrounding living liver donation . As an ultimate treatment, LT has played a crucial role in saving patients with ALF.…”
mentioning
confidence: 99%
“…Additionally, mortality is high without liver transplantation (LT) . Transplantation in pediatric candidates with pediatric acute liver failure (PALF) is a more arduous prospect because technical and logistical features unique to children increase complexity of implantation, including donor/recipient size mismatch, poor availability of pediatric donors, and technical and ethical concerns surrounding living liver donation . As an ultimate treatment, LT has played a crucial role in saving patients with ALF.…”
mentioning
confidence: 99%
“…The main indication for LT in small infants (≤3 months) is ALF secondary to neonatal hemochromatosis . In the present series, this indication accounted for half of the patients in the XS group.…”
Section: Discussionmentioning
confidence: 53%
“…Many of these earlier studies showed that patient survival in the recipients <3 months of age was poorer and, thereby, contributed to the etiology of liver disease being different to that of older infants . However, other studies and present work have refuted this observation . Table summarizes the published literature and present series on LT in small infants ≤3 months old.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations